Comparative study of conservative management of anal fissure with warm sitz bath and warm sitz shower bath - Rathore, Rajesh Kumar (International Surgery Journal, 2019)
Background: Conservative treatment of anal fissure encompasses sitz bath as the prime modality. The present study was conducted to evaluate the comparative outcome of warm sitz bath and warm sitz shower bath among the anal fissure patients. Methods: The present study was prospective comparative evaluation of warm sitz bath and warm sitz shower bath method on 50 anal fissure patients attending the surgery department, Government Medical College, Dungarpur. The fifty patients were divided into two groups (n=25) as patients instructed with warm sitz bath and warm sitz shower bath respectively. The outcome such as pain relief, improvement in symptomatology and satisfaction were evaluated using visual analogue scale for 7 days. Results: The mean age of patients was 31-40 years. The day 1 pain core in warm sitz bath and warm sitz shower bath was found to be 7.54±0.87 and 7.87±0.65 respectively. On day 7 the pain score as significantly (p<0.05) reduced in warm sitz shower bath group as that of the warm sitz bath (2.67±0.47 vs 4.21±0.51) respectively. The patient satisfaction was significantly (p<0.05) higher in patients receiving warm sitz shower bath as that of the warm sitz bath. Further, significant (p<0.05) improvement in symptomology was observed in warm sitz shower bath group as that of warm sitz bath on day 3,5 and 7. Conclusions: Thus, the present study suggests that warm sitz shower bath showed significant efficacy in pain relief and satisfaction as that of the warm sitz bath.